Structure and tunneling magneto-dielectric properties of Co–SrF2 nano-granular thin films - Cheng Wang (AIP Advances, 2021)
Nano-granular thin films with a new composition designed to enhance the tunneling magneto-dielectric (TMD) effect of Co–SrF2 were successfully deposited using the co-sputtering method. This study explored the influence of the crystallinity of the matrix material on nano-granular structures. Cobalt contents were controlled from 0 to 19 at. % by changing the power of the cobalt cathode from 0 to 205 W. The structures in which the Co granules (Φ 3–4 nm) were homogeneously dispersed in the crystallized SrF2 matrix were clearly observed by transmission electron microscopy and its diffraction patterns. The dielectric constant of the Co19–(SrF2)81 thin film peaked at the giant value of 648 and the saturation magnetization peaked at 3.1 kG, but this material still exhibited a TMD response Δε′/ε′0 of 1.0%. For the Co16–(SrF2)84 thin film, the TMD response peaked at 3.5%, which is higher than previously reported. This study confirmed that increased matrix crystallinity can enhance the TMD response. It also provides motivation for other microstructure improvements.